EFFECTIVE METHODS OF TEACHING ENGLISH TO KIDS (International journal of artificial intelligence, 2026)
This article explores various effective methods for teaching English to children, emphasizing the importance of engaging and interactive learning experiences. It discusses the significance of incorporating play-based activities, storytelling, and visual aids to enhance comprehension and retention. Additionally, the article highlights the role of group dynamics and peer interaction in language acquisition. Strategies such as phonics instruction and vocabulary games are examined, along with the benefits of using technology and multimedia resources. Overall, the article provides practical insights for educators aiming to create a stimulating language learning environment for young learners.